How Reliable is a J-sign Severity Scale When Assessing Lateral Patellar Instability? Original Research - Klimenko , Oksana; Sousa, Ted C.; Baker, Ryan; Carl, Jacob; Mader, Shelley; Holden, Kristopher; McMulkin, Mark L. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Patellar instability is a common cause of anterior knee pain and can limit function and sports participation. To help assess patellar instability, the clinical J-sign test consists of observing the patella translate laterally in the shape of an inverted J over the anterolateral femur proximal to the trochlear groove during active knee extension. Only positive or negative categorization of the J-sign test has typically been used without rating the severity. The purpose of this study was to assess the inter- and intra-observer reliability of a proposed grading/severity scale of the J-sign test. Methods: A scale for J-sign severity was developed as follows: grade 0: ≤1 quadrant of translation; grade 1: >1quadrant of translation; grade 2: >2 quadrants of translation; grade 3: complete patellofemoral dislocation; grade 4: unable to complete J-sign due to pain or apprehension. This retrospective cross-sectional study assessed J-sign ratings (0 to 4) from videos of patients undergoing evaluation for patellar instability. Six healthcare professionals rated the severity of the J-sign using the proposed scale, two different times, for all knees presented in random order. Inter- and intra-observer reliability were calculated using a Fleiss Kappa, k. Results: Forty-four patients (87 knees) ages 10-18 were included in this study. Both knees were rated, including unaffected knees to serve as a control. The proposed standardized grading scale for the J-sign had fair agreement for inter-observer reliability, k = 0.31, and moderate agreement for intra-observer reliability, k = 0.58. Conclusion: The proposed scale for determining J-sign severity yielded fair inter-observer reliability moderate intra-observer reliability, similar to the Kappa scores evaluating only the presence or absence of the J-sign. Further study into developing a standardized scale for J-sign severity grading might improve clinical descriptors of the test, and expand on other factors including clarity of knee extension ability, video standardization, and training materials.